2019
DOI: 10.3389/fmicb.2019.02679
|View full text |Cite
|
Sign up to set email alerts
|

From the Vineyard to the Winery: How Microbial Ecology Drives Regional Distinctiveness of Wine

Abstract: Wine production is a complex process from the vineyard to the winery. On this journey, microbes play a decisive role. From the environment where the vines grow, encompassing soil, topography, weather and climate through to management practices in vineyards, the microbes present can potentially change the composition of wine. Introduction of grapes into the winery and the start of winemaking processes modify microbial communities further. Recent advances in next-generation sequencing (NGS) technology have progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 106 publications
3
94
0
1
Order By: Relevance
“…In this study, we demonstrated that microbial biogeographic communities were distinct in both vineyard soils and grape musts in southern Australia regardless of the growing season/vintage. This aligns with previous studies on wine microbial biogeography and provides further evidence for microbial terroir (reviewed by Liu et al [29]) (13,15,19,26). Soil bacteria can be used to distinguish wine-growing regions, with impacts from soil properties (Fig.…”
Section: Figsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, we demonstrated that microbial biogeographic communities were distinct in both vineyard soils and grape musts in southern Australia regardless of the growing season/vintage. This aligns with previous studies on wine microbial biogeography and provides further evidence for microbial terroir (reviewed by Liu et al [29]) (13,15,19,26). Soil bacteria can be used to distinguish wine-growing regions, with impacts from soil properties (Fig.…”
Section: Figsupporting
confidence: 89%
“…Previous work has shown that must and soil community structures are similar and that some Enterobacteriales and Actinomycetales species originate from the soil (8,16). As C/N ratios can be manipulated by composting and cover crops (48), there is an opportunity to manipulate wine microbiota by focusing on vineyard management (29). The soil bacterial microflora is recognized as important for plant growth processes more broadly (49), but fungal diversity beyond endosymbiotic mycorrhizae has not been systematically investigated for grapevines.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we observed significant seasonal microbial variability in M samples ( Supplementary Table S2 ), such as in genera Hanseniaspora and Torulaspora , which showed notable differences in relative abundances among seasons ( Supplementary Table S1 , Figure 1 A). This variability could not be explained by the physicochemical parameters measured in these samples, but rather it might be explained by other environmental factors that we did not evaluate and could have affected the microbial community prior to the harvest, such as temperature, relative humidity and rainfall, among others [ 8 , 15 ]. We noticed that from the 48 total genera present in M samples, the exclusive ones from the first and second seasons of the unfermented musts were represented by few reads, adding only 0.004 and 0.012% of relative abundance, respectively ( Supplementary Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial biogeography contributes to regional distinctiveness of agricultural products, known as "terroir" in viticulture [reviewed by Liu et al (2019)]. Biogeographical patterns in the microbiota associated with the grape and must have been demonstrated for both fungi and bacteria at a regional scale (Bokulich et al, 2014;Mezzasalma et al, 2018;Pinto et al, 2015;Taylor et al, 2014), which are conditioned by multiple factors, such as cultivar, climate and vintage, topography, and soil properties (Bokulich et al, 2014;Liu et al, 2019;Miura et al, 2017;Portillo et al, 2016;Zarraonaindia et al, 2015). Bokulich et al (2016) showed that the bacterial and fungal consortia correlated with metabolites in finished wines, highlighting the importance of fermentative yeasts (for example, S. cerevisiae, Hanseniaspora uvarum, Pichia guilliermondii) and lactic acid bacteria (Leuconostocaceae) on the abundance of regional aromatic signatures.…”
Section: Introductionmentioning
confidence: 99%